2021
DOI: 10.3390/ijerph18063065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19-Related Home Confinement on Sleep Quality, Screen Time and Physical Activity in Tunisian Boys and Girls: A Survey

Abstract: COVID-19 home confinement has led to a stressful situation for children around the world and affected their lifestyle. The present study aimed to investigate the effect of these restrictions on sleep quality, screen time (ST) and physical activity (PA) in Tunisian children with a special focus on gender differences. An online survey was launched in April 2020. Questions were presented in a differential format, with expected responses related to “before” and “during” confinement. Participants (52 boys and 48 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
67
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 59 publications
17
67
2
1
Order By: Relevance
“…Our results demonstrated that compared to the pre-COVID-19 period, weekday MVPA, weekday light PA (LPA), and weekend LPA decreased, whereas weekday and weekend SB increased as measured using an accelerometer during the COVID-19 pandemic. Our results on PA were consistent with the results of a Spanish study 32 and a Chilean study 33 on preschool-aged children, as well as with the results of Tunisian 34 , Chinese 8 , Canadian 9 , US 10 , and German 35 studies on school-aged children between 5 and 17 years of age with different restrictions such as lockdowns. In particular, one notable nding of this study is that LPA and MVPA were affected by COVID-19 and that the levels during weekends and weekdays decreased.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrated that compared to the pre-COVID-19 period, weekday MVPA, weekday light PA (LPA), and weekend LPA decreased, whereas weekday and weekend SB increased as measured using an accelerometer during the COVID-19 pandemic. Our results on PA were consistent with the results of a Spanish study 32 and a Chilean study 33 on preschool-aged children, as well as with the results of Tunisian 34 , Chinese 8 , Canadian 9 , US 10 , and German 35 studies on school-aged children between 5 and 17 years of age with different restrictions such as lockdowns. In particular, one notable nding of this study is that LPA and MVPA were affected by COVID-19 and that the levels during weekends and weekdays decreased.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation is that the reduced physical activity observed in the current study might have a negative impact of children's health. The results of the current study provide objective support to the findings of prior studies using parent-reported questionnaires that investigated the impact of the pandemic in children around the world and found physical activity to be significantly reduced by social distancing restrictions [6][7][8][9][10][11]45,46]. Evidence has already been reported regarding negative short-term health outcomes of the pandemic.…”
Section: Physical Activitysupporting
confidence: 86%
“…However, this method is commonly used and is practical on working participants. The Ricci–Gagnon questionnaire has been used because it has already been used in some studies [ 27 , 39 , 40 , 41 ] and it is known to be very comprehensive and easy to fill. Moreover, in the situation of partial confinement due to the COVID-19, the International Physical Activity Questionnaire (IPAQ) was not appropriate to record the habitual physical activity practice of participants because it focuses only on the physical activity done during the previous 7 days.…”
Section: Discussionmentioning
confidence: 99%